Improved Power Control Based Variable Speed Wind-Turbine DFIG under Hard Work Conditions: Application of Sliding Mode Theory - Itouchene, Hichem; Boudries, Zoubir; Amrane, Fayssal (Periodica polytechnica. Electrical engineering and computer science, 2024)
This paper introduces an efficient and simple power control for the Wind Energy Conversion System (WECS) based on the Doubly-Fed Induction Generator (DFIG). Due to the limitation performance of the conventional PI controller against DFIG parameters change and wind speed variation; the sliding mode theory is applied in order to overcome these drawbacks. To improve the performances of a WECS, robust and nonlinear control techniques, namely; Conventional Sliding Mode Control (C-SMC) and Third Order Sliding Mode Control (3O-SMC), were implemented to independently control the stator active and reactive powers. However, both techniques exhibited a chattering phenomenon, an undesirable phenomenon caused by discontinuous signals. To overcome this drawback and further enhance previous control techniques, an advanced Variable Gain Super Twisting Algorithm (VGSTA) is proposed and compared to SMC and 3O-SMC. Furthermore, to validate the effectiveness of the proposed VGSTA strategy in comparison to two previous control methods, the WECS was simulated and validates using the MATLAB/Simulink environment. The simulation results clearly demonstrated the superiority of the proposed VGSTA strategy over the previous SMC and 3O-SMC techniques. This was obvious in terms of both fast convergence velocity and reduce chattering phenomenon.